КОНЕСКИ И ФОЛКЛОРОТ (Филологические заметки, 2019)
This paper has an objective to analyze the work of Blazhe Koneski and its relation to folklore and oral tradition. Namely, it starts from his lifelong interest in folklore, through his efforts in collection and publication of Macedonian folk creation, to his comprehension of the oral literature as the first phase of the growth of the Macedonian contemporary literature. The central part of the text focuses on Koneski’s essays on subject matters from the history of literature and ranks him as the first Macedonian folklorist. In addition, the paper discusses his connection to some of the dominant literary theories and makes an attempt to present his personal system. At last, the paper views him in the context of the whole Macedonian culture.